The Effectiveness of Sentence Combining Technique in Improving Twelfth-Grade Students’ Writing Ability of Report Texts - Muliani Fitri; Qonaah Nuryan Arif; Esti Raihana (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aimed to investigate the effectiveness of the Sentence Combining Technique in improving the writing ability of twelfth-grade students in writing report texts at SMA Negeri 3 Mandau. The background of this research was based on the observation that many students struggled with vocabulary, grammar, and organization in writing, and English classes were limited to two hours per week. A quasi-experimental design was employed with two groups: an experimental class taught by using the Sentence Combining Technique and a control class taught with conventional methods. Data were collected through pre-tests and post-tests and analyzed using SPSS version 25, including normality, homogeneity, and t-tests. The findings revealed that students in the experimental class showed significant improvement in their writing scores compared to the control class. The mean score of the experimental class increased from 55.31 in the pre-test to 83.46 in the post-test, while the control class only improved from 53.27 to 65.67. The statistical test confirmed that the improvement was significant, indicating that the Sentence Combining Technique was effective in enhancing students’ writing performance, particularly in content, organization, vocabulary, language use, mechanics. The results of this research suggest that teachers may apply the Sentence Combining Technique as an alternative strategy to improve students’ ability to write report texts in senior high school.